1989
DOI: 10.1073/pnas.86.12.4736
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase-negative herpes simplex virus mutants establish latency in mouse trigeminal ganglia but do not reactivate.

Abstract: Herpes simplex virus infection of mammalian hosts involves lytic replication at a primary site, such as the cornea, translocation by axonal transport to sensory ganglia and replication, and latent infection at a secondary site, ganglionic neurons. The virus-encoded thymidine kinase, which is a target for antiviral drugs such as acyclovir, is not essential for lytic replication yet evidently is required at the secondary site for replication and some phase of latent infection. To determine the specific stage in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

25
306
1
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 339 publications
(335 citation statements)
references
References 55 publications
25
306
1
3
Order By: Relevance
“…Although a number of viral genes are necessary for neurovirulence the deletion of some of these such as those encoding ICP6 or thymidine kinase does not provide an absolute block to replication in the brain and they are thus not suitable for production of viral vectors. 12,13 However, the ICP34.5 protein has been shown to be absolutely required for a neurovirulent phenotype. Thus ICP34.5 deletion mutants have an LD 50 of Ͼ10 6 p.f.u.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of viral genes are necessary for neurovirulence the deletion of some of these such as those encoding ICP6 or thymidine kinase does not provide an absolute block to replication in the brain and they are thus not suitable for production of viral vectors. 12,13 However, the ICP34.5 protein has been shown to be absolutely required for a neurovirulent phenotype. Thus ICP34.5 deletion mutants have an LD 50 of Ͼ10 6 p.f.u.…”
Section: Introductionmentioning
confidence: 99%
“…The former mechanism is most frequently seen in the clinic (8,16,17,29), probably because TK is not essential for viral replication in most tissues and culture cells (36). However, several reports have demonstrated that TK activity facilitates HSV reactivation from latency in neural ganglia (11,13,44,46).Changes in the TK gene can result in viruses producing no or partial amounts of TK or with an altered substrate specificity (4, 23). Darby et al have proposed a preliminary model for the active center of the HSV type 1 (HSV-1) TK enzyme including three distinct regions: an ATP-binding site (amino acids 51 to 63), a nucleoside-binding site (amino acids 168 to 176), and amino acid 336 (12).…”
mentioning
confidence: 99%
“…One of the earliest studies using a thymidine kinase (TK)-negative HSV mutant dlsptk (Coen et al, 1989) demonstrated a dose-dependent improvement in survival of nude mice bearing intracranial tumours following intratumoral therapy (Martuza et al, 1991). However, subsequent studies demonstrated that this mutant is unsuitable for therapeutic use in humans as it can cause encephalitis.…”
Section: Discussionmentioning
confidence: 99%